Research on heat transfer mechanism and performance of a novel adaptive enclosure structure based on micro-channel heat pipe. (1st September 2022) - Zheng, Senlin; Qiu, Zining; He, Caiwei; Wang, Xianling; Wang, Xupeng; Wang, Zhangyuan; Zhao, Xudong; Shittu, Samson
Abstract: In this paper, a novel adaptive enclosure structure (AES) combining the building wall and heat pipe is proposed for building wall energy saving. The theoretical heat transfer process of the structure is analyzed, and its heat transfer performance is obtained. The theoretical thermal resistance of the structure is about 0.165 K/W. The one-dimensional steady-state heat transfer experiment has been carried out. Under the temperature difference of 35 °C, the surface temperature of the AES is much higher than that of the traditional wall on the heating demand side (about 9.5 °C). The heat transfer experiment under the influence of multiple factors has been carried out. Under heating demand, the indoor side surface temperature of the AES is higher than that of the traditional wall (about 1.5 °C). Under cooling demand, the indoor side surface temperature of the structure is lower than that of the traditional wall (about 0.8 °C). In addition, it is realizable to switch the performance of the AES between efficient heat transfer or good thermal insulation according to requirements. The proposed structure has great potential for reducing the indoor energy consumption and improving thermal comfort, and could provide a new solution for passive energy-saving technology based on building envelope. Highlights: An adaptive structure based on heat pipes is proposed for building energy saving. A method combining heat pipe and wall with less impact on the structure is proposed. The thermal resistance of the structure is 0.165 K/W, 2% of the traditional structure. The change of heat transfer performance based on the environment can be realized. The switching schemes of the heat transfer in four seasons is proposed and analyzed.